2009
DOI: 10.1128/iai.00405-09
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Protection against Botulinum Neurotoxin Intoxication in Mice

Abstract: Adulteration of food or feed with any of the seven serotypes of botulinum neurotoxin (BoNT) is a potential bioterrorism concern. Currently, there is strong interest in the development of detection reagents, vaccines, therapeutics, and other countermeasures. A sensitive immunoassay for detecting BoNT serotype A (BoNT/A), based on monoclonal antibodies (MAbs) F1-2 and F1-40, has been developed and used in complex matrices. The epitope for F1-2 has been mapped to the heavy chain of BoNT/A, and the epitope of F1-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
73
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 31 publications
11
73
0
Order By: Relevance
“…A recent study in which mice were orally intoxicated with botulinum neurotoxin serotype A (BotA) and then treated by passive Ab transfer demonstrated that differences of just 1 to 2 h in antibody administration time points resulted in the loss of the capacity to rescue intoxicated animals (44). We speculate, therefore, that as with BotA, once Stx2a is sequestered in target tissues (the kidneys), passive Ab transfer is not able to rescue intoxicated animals.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study in which mice were orally intoxicated with botulinum neurotoxin serotype A (BotA) and then treated by passive Ab transfer demonstrated that differences of just 1 to 2 h in antibody administration time points resulted in the loss of the capacity to rescue intoxicated animals (44). We speculate, therefore, that as with BotA, once Stx2a is sequestered in target tissues (the kidneys), passive Ab transfer is not able to rescue intoxicated animals.…”
Section: Discussionmentioning
confidence: 90%
“…While cooperativity and synergism of monoclonal antibody mixtures have been reported in the past (16)(17)(18)(19), emerging data have illustrated striking examples of situations wherein the activity of a monoclonal antibody can be drastically altered when assessed in the context of other antibodies (20,21). Indeed, the benefits of using polyclonal antibody preparations to treat disease in therapeutic settings are just beginning to be realized (22).…”
mentioning
confidence: 99%
“…High valency of binding may be important in multiple respects for Tcd neutralization. First, antigens decorated with multiple antibody Fc domains are cleared faster and more effectively from circulation than those bearing one MAb/Fc (72,73), and such clearance can contribute significantly to neutralization potential in vivo (65). Since circulating toxin has been suspected in patients (74,75) and has been demonstrated in a piglet model of infection (76), improved toxin clearance may offer clinical advantage to some patients.…”
Section: 88mentioning
confidence: 99%